FIT AND STYLE MODIFICATION OF APPAREL USING PATTERN DRAFTING AND FREE-HAND CUTTING AMONG INFORMAL DRESSMAKERS AND TAILORS - Bakker-Edoh , Dr. Dymphna; Ancelm Kereth, Gudila; Kofi Kassah, Dr. Johnson; B. Oigo , Dr. Elizabeth; G. Mburugu, Prof. Keren (International Journal of Fashion and Design, 2021)
Purpose: To assess the fit and style modification of apparel using pattern drafting and free-hand cutting among informal dressmakers and tailors. Methodology: Design and style modification were measured using a composite score based on the observation checklist of the finished products of apparel made from both free-hand and pattern drafting technique. There was an agreement between the respondents and the researcher on a common style. One of the styles was to check for fit and others for fit and style modification respectively. The finished product from both methods was analyzed on live models to check on the stitches and seam, arrangement of fullness, application of fastenings, arrangements and position of motifs in the fabric as well as the design details that conform to fit standard based on the checklist used by judges. Special areas of apparel that add up to total fit were identified and assessed. These special areas were the most highly ranked and scored by the judges. Findings: Sheath dresses constructed using both pattern drafting and free-hand cutting were worn by models for evaluation by the judges. All the five judges indicated that the neckline of the sheath dress made with pattern drafting had no problem giving it a 100% score. The shoulder line of the sheath dress made with free-hand cutting was considered as too long by four (80%) out of the five judges. The implication is that the shoulder line of the sheath dress made with pattern drafting was accepted to be the best. The bust of the sheath dress of both methods was seen to be good by the judges, one (20%) indicated that the sheath dress made with pattern drafting was too tight while another one (20%) also claimed it was too loose with respect to the sheath dress made with free-hand cutting. There was a vast difference in the nape to waist section of the sheath dress made with free-hand cutting as compared to that of the pattern drafting resulting to ill-fitting that amounted to puckering at the back of the dress made with free-hand cutting. Unique Contribution to theory, practice and policy: Additionally, an apparel made using Free-hand cutting apparel was superior in areas such as the length of the apparel and fixing of fasteners as compared with pattern drafted apparel. The study therefore recommended the need to develop and train pattern drafting since it bring success into the apparel construction industry and over-reliance on free-hand cutting could keep some dressmakers and tailors out of business with time.